2013
DOI: 10.1088/0004-637x/768/1/72
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clumps and Infrared Clusters in the S247, S252, and Bfs52 Regions

Abstract: We present results of the observations carried out toward the S247, S252, and BFS52 H ii regions with various molecular lines using the 1.85 m radio telescope and the 45 m telescope at Nobeyama Radio Observatory. There are at least 11 young infrared clusters (IR clusters) within the observed region. We found that there are two velocity components in 12 CO (J = 2-1), and also that their spatial distributions show an anti-correlation. The IR clusters are located at their interfaces, suggesting that two distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 65 publications
(154 reference statements)
5
41
0
Order By: Relevance
“…where V in (x) is the inward velocity, and σ(x) and T ex (x) are the velocity dispersion and excitation temperature of 13 CO. J RJ is a function given in Equation (3), and τ (x, V ) and S(x, V ) are the optical depth per unit length and the total optical depth to the observer. τ 0 (x) is the peak optical depth that can be derived from the number density of molecular hydrogen n(x), the excitation temperature T ex (x), and the fractional abundance of 13 CO (e.g., Shimoikura et al 2013). In this paper, we assume the fractional abundance to be [ 13 CO]/[H 2 ] = 2 × 10 −6 (Dickman 1978).…”
Section: A Model For the Inward Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…where V in (x) is the inward velocity, and σ(x) and T ex (x) are the velocity dispersion and excitation temperature of 13 CO. J RJ is a function given in Equation (3), and τ (x, V ) and S(x, V ) are the optical depth per unit length and the total optical depth to the observer. τ 0 (x) is the peak optical depth that can be derived from the number density of molecular hydrogen n(x), the excitation temperature T ex (x), and the fractional abundance of 13 CO (e.g., Shimoikura et al 2013). In this paper, we assume the fractional abundance to be [ 13 CO]/[H 2 ] = 2 × 10 −6 (Dickman 1978).…”
Section: A Model For the Inward Motionmentioning
confidence: 99%
“…If we take c s = 0.26 km s −1 as derived in the previous subsection, we get M vir ≃ 30 M ⊙ pc −1 . The Virial mass should decrease to half of this value at most (M vir ≃ 15 M ⊙ pc −1 ) if the filament is surrounded by a high external pressure, which is often seen among small dark clouds with a mass of a few hundred solar masses (e.g., Dobashi et al 1996Dobashi et al , 2001Yonekura et al 1997;Shimoikura et al 2013Shimoikura et al , 2018. On the other hand, the C 18 O map in Figure 8 infers the molecular mass and the length of TMC-1 of ∼ 200 M ⊙ and 1 pc, indicating that the actual mass of the filament per unit length M c is an order of 200 M ⊙ pc −1 , which is several times larger than M vir .…”
Section: Gravitational Stabilitymentioning
confidence: 99%
“…Additional possible cases of multiple O star formation triggered by a cloud-cloud collision are reported for M42 , NGC 6334-NGC 6357 (Fukui et al 2017c), M17 (Nishimura et al 2017a), W49A (Miyawaki et al 1986, 2009, Buckley & Ward-Thompson 1996, W51 (Okumura et al 2001;Kang et al 2010 ;Fujita et al in preperation) and R136 (Fukui et al 2017a). In addition to above, many star forming regions and dense clumps in the Milky Way have been suggested to be triggered by a cloud-cloud collision, LkHα198 (Loren 1977); IRAS 19550+3248 (Koo et al 1994); IRAS 2306+1451 (Vallee 1995); M20 (Torii et al 2011(Torii et al , 2017a; RCW120 (Torii et al 2015); N37 (Baug et al 2016); GM 24 (Fukui et al 2017d); M16 (Nishimura et al 2017b); RCW34 (Hayashi et al 2017); RCW36 (Sano et al 2017a); RCW166 (Ohama et al 2017a); S116, S117, S118 (Fukui et al 2017e); RCW79 (Ohama et al 2017c); Sh2-48 (Torii et al 2017); NGC 2024 (Ohama et al 2017b); NGC 2068, NGC 2071 (Tsutsumi et al 2017); NGC 2359 (Sano et al 2017b); S87 (Xue & Wu 2008); S87E, S88B, AFGL 5142, AFGL 5180 (Higuchi et al 2010); G0.253+0.016 (Higuchi et al 2014); Circinus-E cloud (Shimoikura & Dobashi 2011); Sh2-252 (Shimoikura et al 2013);L1641-N (Nakamura et al 2012; Serpens Main Cluster (Duarte-Cabral et al 2011); Serpens South (Nakamura et al 2014); L1004E in the Cygnus OB 7 (Dobashi et al 2014); G35.20-0.74 (Dewan...…”
Section: Cloud-cloud Collisions As a Trigger Of High-mass Star Formationmentioning
confidence: 99%
“…NCS has a molecular mass of ∼ 1 × 10 3 M⊙ in total which is a typical mass of clumps forming young clusters (e.g., Saito et al 2007;Shimoikura et al 2013). According to our recent statistical studies of cluster forming clumps (Shimoikura et al 2016(Shimoikura et al , 2018a, the clump-scale collapsing motion with rotation as found toward NCS is commonly observed in an early stage of cluster formation.…”
Section: Introductionmentioning
confidence: 99%